PLS-SEM Modeling of the Relationship Between University Service Quality and Student Satisfaction: Evidence from a Peruvian Public University - Carlos, Torres Sifuentes; Oscar, Tinoco Gómez; Karol, Moore Torres, Rosa; Pablo, Rosales Lopez, Pedro (Journal of Posthumanism, 2025)
To determine the influence of university service quality on student satisfaction at a public university in Lima during the year 2023. The study designs and validates a formative model supported by an appropriate data collection instrument to assess the most relevant dimensions in the context of public universities. The research follows a quantitative approach, with a non-experimental, cross-sectional, and correlational-causal design. A data collection instrument (Likert-type survey) was developed, and content validity was assessed by expert judgment using Aiken’s V coefficient and confidence interval methods. Reliability analysis was conducted through Cronbach’s alpha internal consistency method. A multivariate analysis was carried out with 85 undergraduate students enrolled in the tenth academic term of the School of Industrial Engineering, Faculty of Industrial Engineering at the National University of San Marcos (UNMSM), each registered for a minimum of 12 academic credits. Partial Least Squares Structural Equation Modeling (PLS-SEM) was then performed. The instrument (questionnaire) was validated, and the model’s validity and reliability were confirmed. The results indicate that service quality has a positive and significant relationship (0.919) with student satisfaction in the structural model.